AKSELERASI KINERJA UMKM: PERAN STRATEGIS FINANCIAL LITERACY DI ERA DIGITAL - Shanti, Elena Rista Kurnia; Mangifera, Liana (POLITEKNIK LP3I JAKARTA, 2026)
The decline in the number of active MSMEs in Boyolali Regency indicates obstacles in business performance, thus requiring financial literacy in the use of fintech and financial behaviour to improve MSME performance in a sustainable manner. The purpose of this study is to analyse the role of financial literacy in mediating the influence of financial behaviour and financial technology on SME performance in Boyolali Regency, with financial literacy as the mediator. This study uses a quantitative approach and primary data was collected from 140 SME actors through a questionnaire distributed using purposive sampling techniques. Data analysis was conducted using the PLS-SEM method. The research findings indicate that financial behaviour and financial literacy have a significant positive effect on MSME performance, while financial technology has a significant negative effect. Financial behaviour and financial technology have a significant positive effect on financial literacy. Furthermore, the effect of financial behaviour on MSME performance is partially mediated by financial literacy, while the effect of financial technology on MSME performance is fully mediated by financial literacy. It is hoped that these findings will enrich our understanding of how financial behaviour, financial technology and financial literacy influence the performance of MSMEs, and contribute fully to MSME actors and stakeholders in designing financial management strategies and policies for the sustainability of MSME performance.